PENERAPAN MODEL PEMBELAJARAN PICTURE AND PICTURE UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SEKOLAH DASAR - Wiyati, Wiyati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
The background of this research is the low reading ability of the first graders of SDN 019 Bumi Ayu. Of the 47students who received low category there were 35 students (74,46%), medium category there were 11 students(23,40%) and high category 1 student (2,12%) with average value 49,47. The purpose of this research is toimprove students' reading ability of Class I SDN 019 Bumi Ayu by applying cooperative learning model ofpicture and picture type. The result of the research is the first data of the low categorized students, there are 35students (74,46%), the students are there are 11 students (23,40%) and the high categorized students are 1student (2,12%) with average 49.47 is low category. In the first cycle students' reading ability increases. Lowcategorized students were 29 students (61.70%), students were categorized by 13 students (27.65%) and highcategorized students were 5 students (10.63%) with an average rating of 64.36 categorized low. In the secondcycle again increased the ability of reading students. The low categorized students were reduced to 17 students(36.17%), the categorized students were increased to 15 students (31.91%) and the high category also increasedto 16 students (34.04%) average 79.43 is moderate category.